Analisis financial distress menggunakan metode springate pada perusahaan heathcare yang terdaftar di bei tahun 2019-2022 - Khoiriyah, Ikhda Rofiqotul (Maliki Interdisciplinary Journal, 2025)
This research aims to analyze the potential for financial distress in health sector companies listed on the Indonesia Stock Exchange (BEI) using the Springate method. The background to this research is the importance of the healthcare sector in supporting the welfare of the Indonesian people, especially after the COVID-19 pandemic which has increased demand for health services. Financial distress is a financial crisis condition that can lead to bankruptcy if not treated immediately. The Springate method, which adopts Multiple Discriminant Analysis (MDA), is used in this research to calculate the S-score value in the financial report data of healthcare companies for the 2019-2022 period. This research is quantitative descriptive, using secondary data which is processed to produce an S-score as an indicator of a company’s financial health. The research results show that the companies studied have different S-score variations, indicating that some are financially healthy and some are at risk of financial distress. It is hoped that these results can be a reference for company management in making strategic decisions as well as for investors in assessing investment risks in the healthcare sector in Indonesia.